Does state self‐control depletion predict relationship functioning and partner aggression? An ecological momentary assessment study of community couples. Issue 6 (11th July 2020) - Testa, Maria; Wang, Weijun; Derrick, Jaye L.; Crane, Cory; Leonard, Kenneth E.; Collins, R. Lorraine; Hanny, Courtney; Muraven, Mark
Abstract: Intimate relationship functioning depends upon the ability to accommodate one's partner and to inhibit retaliatory and aggressive impulses when disagreements arise. However, accommodation and inhibition may be difficult when self‐control strength is weak or depleted by prior exertion of self‐control. The present study considered whether state self‐control depletion prospectively predicts male and female self‐reports of anger with partner and arguing with partner. Consistent with the I 3 Model (Finkel, 2014, Adv Exp Soc Psychol, 49, 1–104), we also considered whether the association between elevated anger and arguing (i.e., instigation) and partner aggression was stronger when state self‐control (i.e., inhibition) was depleted or among people high in negative urgency. In this ecological momentary assessment (EMA) study, heavy drinking married and cohabiting heterosexual couples ( N = 191) responded to three randomly signaled reports each day for 30 days. Depletion predicted anger and arguing with partners both cross‐sectionally and prospectively for men and women. However, after controlling for prior levels of anger and arguing, these effects were diminished, and supplemental analyses revealed that anger and arguing with partner predicted subsequent depletion. Anger and arguing were strongly associated with concurrent reports of partner aggression perpetration and victimization (verbal and/or physical). However, neither state self‐control depletion nor negative urgency moderated these effects. Overall, results suggest a modest impact of depletion on daily couple functioning as well as a potential cyclical effect of arguing on depletion.